Regional Wage Differences in Manufacturing in the Postwar Period - Segal, Martin (The Review of Economics and Statistics, 1961)
I NTER-REGIONAL wage differences have traditionally constituted an important aspect of the analysis of the wage structure of the United States. But, despite continuing interest in the subject, there has been no comprehensive examination of the course of such differences since World War II.' The present paper attempts to fill this gap, at least partly. Specifically, the paper examines the changes in the pattern of regional wage differences in manufacturing between I947 and I954, and considers the major factors responsible for these changes. The wage statistics used are average hourly earnings of I93 so-called digit industries. These statistics were derived from the data on gross earnings of production workers and on manhours worked, published in the U.S. Census of Manufactures for I947 and I954. From these data I computed for each industry regional average hourly earnings in the four broad regions of the countryNortheast, North Central, South, and West.2 The Pearsonian coefficient of variation was used to measure the degree of difference of earnings among the four regions. Comparison of the I947 and I954 coefficients for each industry thus indicated the change in the interregional dispersion of average earnings. In terms of employment of manufacturing production workers the coverage of the study is quite large. The I93 industries for which it was possible to make a meaningful comparison of regional wage differentials in both years employed in I954 6,984,000 workers. This figure represents 56.5 per cent of all manufacturing workers in that year.3